Pasantías de ingeniería civil en la secretaría de planeación y desarrollo territorial del municipio de San Francisco Cundinamarca (2021)
In the first weeks we performed activities of filing and printing of resolutions requested by a court to be delivered physically to Mr. Lugerio Huertas, in most of the internship was performed in an administrative way some activities such as settlement of agreements and contracts with the Colombian Institute of infrastructure, creation of certifications of public services, among some others already named in the log of daily activities carried out, all under the activities included in the resolution created to perform the internship in the municipality of San Francisco Cundinamarca.